2005
DOI: 10.1089/acm.2005.11.793
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic Treatment for Chronic Disease: A 6-Year, University-Hospital Outpatient Observational Study

Abstract: Homeopathic intervention offered positive health changes to a substantial proportion of a large cohort of patients with a wide range of chronic diseases. Additional observational research, including studies using different designs, is necessary for further research development in homeopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 35 publications
5
98
1
9
Order By: Relevance
“…La aplicación óptima se da en el diagnóstico y tratamiento en un amplio rango de enfermedades crónicas (17) . Aquí existe un claro posicionamiento.…”
Section: Potencial De Desarrollounclassified
“…La aplicación óptima se da en el diagnóstico y tratamiento en un amplio rango de enfermedades crónicas (17) . Aquí existe un claro posicionamiento.…”
Section: Potencial De Desarrollounclassified
“…In this study, carried out over a six-year period, 70% of patients reported an improvement in their health. 5 Despite the article's claim that it is seeking to provide a summary of the science of homeopathy, it does no such thing. While it is true to say that scientists cannot yet explain the precise mechanism of action of homeopathic remedies, D. Shaw merely jumps on a bandwagon of dismissing homeopathy out of hand.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Some complementary therapists already argue that observational studies without a control group might provide valuable data about the effectiveness of their intervention. 4 Whenever disappointing results from pragmatic trials emerge, this approach can be used to turn the negative into a (false) positive. It is able to generate positive outcomes purely on the strength of the natural history of diseases and the regression towards the mean.…”
Section: The Anarchy Of Evidencementioning
confidence: 99%